Depleting of Tropical Forest at a Landscape Scale: Finding Solutions for Bangladesh - Kibria, M.G.; Sunderland, T.; Rahman, S.A.; Imtiaj, A. (Our Nature, 2011)
Drastic deforestation is a major problem of Bangladesh which is contributing to negative downstream impacts on the environment. To address this problem various measurements should be taken at different scales. The main objective of this study is to suggest the possible steps that Bangladesh could halt and reverse the trend of deforestation. An extensive literature review and interviews with government officials, professionals and NGO workers have been used to collect relevant information on the drivers of deforestation in the country. Based on the information gathered, this paper presents the reasons and extent of deforestation, and suggests some positive steps where the Government could be the main mitigating performer by implementing integrated programmes, which will also ensure mass awareness and wider impact. Local NGOs and international bodies must also formulate adequate plans to protect valuable areas of remaining forest. DOI: 10.3126/on.v8i1.4340